'Delicioso Precoce' - a new IAC's late blooming selection for cold areas of São Paulo, Brazil - Campo Dall'orto, Fernando Antônio; Ojima, Mário; Barbosa, Wilson; Picarelli Martins, Fernando; Rigitano, Orlando (Pesquisa Agropecuaria Brasileira, 2014)
'Delicioso precoce' IAC 5174-14 is a new peach cultivar developed by IAC, SP, Brazil, through the crossing of 'Supermel' - a local dessert peach selection and 'Sunred' - a nectarine coming from Florida, USA. Its fruits are big (90 g to 120 g), with white flesh, freestone, slightly acid-sweet taste (Brix 13º and pH 4.2) an atractive red skin and different shades of pink and light red, covering 50% to 60% of its surface. Its moderate chilling requirement, late flowering and high productivity of early ripening handsome fruits of great uniformity, are the most important characteristics which justify its inclusion in some commercial peach areas of São Paulo, Brazil, mainly where late winter frost may cause damage.
Keywords: each breeding; white flesh; freestone fruit; moderate chilling requirement; late flowering.